Service quality and customer loyalty in halal ethnic restaurants amid the COVID-19 pandemic: a study of halal Uzbekistan restaurants in South Korea - Azam Kayumov; Young-joo Ahn; Kiattipoom Kiatkawsin; Ian Sutherland; Seweryn Zielinski (Cogent Social Sciences)
This present study examined which service quality factors and the COVID-19 were related to overall satisfaction. Moreover, it explored whether customers’ satisfaction increased their loyalty toward halal ethnic restaurants. This study examined which service-quality factors were related to overall satisfaction. Moreover, it explored whether customers’ satisfaction increased their loyalty toward halal ethnic restaurants during the COVID-19 pandemic. The data were collected from a total of 227 respondents. The results show that the dimensions of service quality consist of five factors, namely, COVID-19 safety, employee service, ambience, cleanliness, and food quality. Cleanliness and food quality positively influence overall satisfaction. One factor, obligatory safety (COVID-19 safety), however, has a negative effect on overall satisfaction. Furthermore, employee service and ambience does not show a statistically significant effect on overall satisfaction. Finally, overall satisfaction positively influences loyalty. The results also reveal the following: customers might prefer voluntary participation in strict regulations for reducing the transmission of COVID-19 at restaurants; cleaning tables and checking clean dishes should be regularly enforced during restaurant operations; food quality was an important component; for small ethnic restaurants with limited financial investment in digitalization, improving food quality could be a key factor for increasing their positive evaluations and their customers’ loyalty. The results provide empirical evidence that expands the literature on halal ethnic restaurants.